La utilización de las técnicas grafo-plásticas para mejorar la motricidad fina en el desarrollo de las niñas y niños de inicial dos de la escuela fiscal mixta Dr. Edison Calle Loaiza de la ciudad de Loja, período 2014-2015 - Peña Díaz, María de los Ángeles (2016)
The topic of this research is THE USE OF THE TECHNIQUES GRAFO-PLASTIC TO IMPROVE THE FINE MOTOR IN THE DEVELOPMENT OF CHILDREN FROM INITIAL TWO OF THE DR. EDISON CALLE LOAIZA FISCAL MIXED SCHOOL IN LOJA CITY, PERIOD 2014-2015. The general objective to be raised is: Determine the graph-art techniques such as torn, wrinkled, modeling clay and dactyl paint to develop fine motor skills in children from 4 to 5 years of initial two on the Dr. Edison Calle Loaiza Fiscal Primary School in Loja City, period 2014-2015. The research methodology consists of the study of descriptive and correlational type, the methods used were: Inductive qualitative and analytic- synthetic; the technique used was a survey with the purpose to achieve the objectives of the research project., through it can be recognized the people opinions selected of the total population of 30 led to two teachers: one from the initial level I and other of initial level II; as an instrument the test Dexterímetro Goddard to determine the development of fine motor skills apllied to 28 children: 15 girls and 13 children, so the most relevant results was of one child representing 4% who is in a higher level and 9 children representing the 32% considered good. It was concluded that the graph-art techniques such as torn, wrinkled, modeling clay and dactyl paint are a didactic resource that contribute to the development of coordination of movements of both hands and early pre-writing children